The DNA/RNA ratio as a useful indicator of the nutritional condition in juveniles of Ruditapes decussatus - Chícharo, Luís (1995)
Condition indices have been widely used to assess how healthy individuals are under certain circumstances. It has been shown that the RNA/DNA ratio is a good indicator of the nutritional condition of severa1 marine organisms. A very sensitive fluorometric method for RNA/DNA quantification (Clemmesen, 1990) was applied to fed and starved post-larvae laboratory-reared clam, Ruditapes decussatus. The presented study shows that the RNA/DNA ratio is a useful indicator of nutritional stress for bivalve spat. The decrease in RNA/DNA ratio recorded here, under starved conditions was lower than in similar experiments on fish. A lower metabolic rate in clams may result in a slower response with respect to RNA/DNA ratios than that observed in vertebrates.